2009
DOI: 10.1192/bjp.bp.108.054742
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality, causes of death and prognostic factors in anorexia nervosa

Abstract: Anorexia nervosa is characterised by high lifetime mortality from both natural and unnatural causes. Assessment and treatment of psychiatric comorbidity, especially alcohol misuse, may be a pathway to better long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
290
5
17

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(327 citation statements)
references
References 48 publications
15
290
5
17
Order By: Relevance
“…Recent studies found a 75% of recovery rate in anorexia nervosa, although only less than 50% of diagnosed cases were totally asymptomatic (60% in bulimia nervosa) (Jäger et al, 2004;Wade et al, 2006). The introduction of specialized care units for these disorders in some countries seems to have improved patients' survival, particularly in anorexia nervosa (Lindblad et al, 2006;Papadopoulos et al, 2009). However, it cannot be ruled out that, due to the study method, the most severe cases of anorexia and bulimia nervosa were not included in the study sample, since they were hospitalized or unwilling to participate in an investigation on emotional problems.…”
Section: Course Of Eating Disordersmentioning
confidence: 99%
“…Recent studies found a 75% of recovery rate in anorexia nervosa, although only less than 50% of diagnosed cases were totally asymptomatic (60% in bulimia nervosa) (Jäger et al, 2004;Wade et al, 2006). The introduction of specialized care units for these disorders in some countries seems to have improved patients' survival, particularly in anorexia nervosa (Lindblad et al, 2006;Papadopoulos et al, 2009). However, it cannot be ruled out that, due to the study method, the most severe cases of anorexia and bulimia nervosa were not included in the study sample, since they were hospitalized or unwilling to participate in an investigation on emotional problems.…”
Section: Course Of Eating Disordersmentioning
confidence: 99%
“…Unfortunately, there is no Swedish data to show whether or not young people's sleeping habits have in fact changed. However, a Finnish study has found that the percentage of 15-year-olds who go to bed after 11 pm has risen significantly, from around 20 is likely that young Swedish people are also going to bed later in the evening. In 1979-2005, the percentage of young people with sleeping problems rose from 10 to 24 per cent of women aged 16-24 and from 8 to 16 per cent of men of the same age, according to the Survey of Living Conditions (ULF).…”
Section: … and Less Sleepmentioning
confidence: 99%
“…In addition, comorbid diseases such as depression, suicidal behavior, and alcohol addiction are also associated with mortality. A previous study has shown that a younger age at first diagnosis and longer duration of first hospital stay are associated with a better prognosis [5]. Even so, findings are contradictory.…”
Section: Introductionmentioning
confidence: 98%